Financial Inclusion, Financial Literacy, and Financial Performance of SMEs: The Role of Digital Finance Interventions in West Java - Erik Sopian; Nugraha Nugraha; Ika Putera Waspada; Maya Sari (Politeknik Siber Cerdika Internasional, 2026)
Objective: This study aims to study the impact of financial inclusion and financial literacy on the financial performance of small and medium-sized enterprises, where digital finance is the main criterion. Methods: Using a quantitative survey method targeting 178 SME operators in West Java, structural equation modeling analysis based on the partial quadratic method (SEM-PLS) was applied. Results: Financial inclusion and financial literacy have a positive and significant impact on digital financial adoption. Similarly, financial literacy has a positive and significant impact on financial performance. On the other hand, financial inclusion and digital finance did not have a significant direct impact on financial performance, and the intermediate effects of digital finance were not statistically confirmed in this study. The study concludes that the improvement of SME financial performance is not only determined by formal access and adoption of trading techniques, but also by internal financial management capabilities. The novelty of this research is the integration of dynamic efficiency theory in the context of microfinance management, where dynamic competencies exist in the development of frameworks. Conclusion: While the academic implications underscore the need to restructure the intermediation model in the fintech literature for SMEs, the practical implications drive a shift towards digital financial policy towards real economic value creation. Future research should incorporate design variables and longitudinal adjustments according to the characteristics of the business unit.